2016
DOI: 10.21101/cejph.a4084
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Oral Health Behaviour among Scandinavian and Polish Medical Students Studying in Poland

Abstract: SUMMARYAim: The aim of the study was to assess the self-reported oral health behaviour of Scandinavian and Polish medical students studying in Poland. Methods: Three hundred and fifty subjects took part in the questionnaire survey. They were the 4th to 6th year Scandinavian and Polish medical students attending the same medical school. Test-retest reliability demonstrated an accepted level of kappa > 0.50. The questionnaire comprised issues dealing with demographics, dental health behaviour, fluoride tablet re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…The present study results revealed that Women, the more highly educated and those with higher OHL reported brushing their teeth more frequently. The present findings are in line with those of previous studies showing that higher socioeconomic status, [27,28] OHL scores, [4,14,15] and gender [28][29][30] relate to more frequent tooth brushing. Gender differences in brushing habits may stem from women's desire to be more socially attractive.…”
Section: Tooth Brushingsupporting
confidence: 93%
“…The present study results revealed that Women, the more highly educated and those with higher OHL reported brushing their teeth more frequently. The present findings are in line with those of previous studies showing that higher socioeconomic status, [27,28] OHL scores, [4,14,15] and gender [28][29][30] relate to more frequent tooth brushing. Gender differences in brushing habits may stem from women's desire to be more socially attractive.…”
Section: Tooth Brushingsupporting
confidence: 93%
“…Although Europe has experienced a decrease in the number of caries lesions overall, mostly by including preventive measures as health strategies, there are still notable differences regarding the state of oral health among its countries . On a national level, oral health is dependent on the economic situation, on the social and cultural determinants and, most importantly, on the health system and strategy of that country …”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3,4] reported gender difference of health habits including oral hygiene. Kawamura, et al [4] showed that females have better oral hygiene practices, whereas males have unpleasant subjective symptoms such as tooth mobility.…”
Section: Discussionmentioning
confidence: 99%